From Strong Dichroic Nanomotor to Polarotactic Microswimmer. Issue 48 (7th October 2019) - Zhan, Xiaojun; Zheng, Jing; Zhao, Yang; Zhu, Bairen; Cheng, Rui; Wang, Jizhuang; Liu, Jun; Tang, Jiang; Tang, Jinyao
Abstract: Light‐driven micro/nanomotors are promising candidates for long‐envisioned next‐generation nanorobotics for targeted drug delivery, noninvasive surgery, nanofabrication, and beyond. To achieve these fantastic applications, effective control of the micro/nanomotor is essential. Light has been proved as the most versatile method for microswimmer manipulation, while the light propagation direction, intensity, and wavelength have been explored as controlling signals for light‐responsive nanomotors. Here, the controlling method is expanded to the polarization state of the light, and a nanomotor with a significant dichroic ratio is demonstrated. Due to the anisotropic crystal structure, light polarized parallel to the Sb2 Se3 nanowires is preferentially absorbed. The core–shell Sb2 Se3 /ZnO nanomotor exhibits strong dichroic swimming behavior: the swimming speed is ≈3 times faster when illuminated with parallel polarized light than perpendicular polarized light. Furthermore, by incorporating two cross‐aligned dichroic nanomotors, a polarotactic artificial microswimmer is achieved, which can be navigated by controlling the polarization direction of the incident light. Compared to the well‐studied light‐driven rotary motors based on optical tweezers, this dichroic microswimmer offers eight orders of magnitude light‐intensity reduction, which may enable large‐scale nanomanipulation as well as other heat‐sensitive applications. Abstract : An Sb2 Se3 ‐nanowire‐based nanomotor shows strong dichroic response due to its highly anisotropic crystal structure. A polarotactic artificial microswimmer is realized by cross‐assembling two Sb2 Se3 nanomotors, and can be navigated by controlling the polarization direction of the light.